Two fouling Olifantiella (Bacillariophyceae) species from the northwest temperate Pacific coast. Issue 3 (3rd July 2019) - Jung, Seung Won; Park, Joon Sang
Abstract : Two naviculoid diatoms with an internal tubular process that opens externally through a pore or process on the valve face were observed on the hull of R/V Onnuri of the Korea Institute of Ocean Science & Technology in South Korea. Owing to the presence of distinctive morphological features, namely the buciniportula and an internal marginal canal, these diatoms were assigned to the genus Olifantiella, which was recently described from tropical regions. Of these two species, one ( Olifantiella onnuria sp. nov.) is new to science. It can be distinguished from other Olifantiella species by two, internally closed, bean-like buciniportulae, and an external T-shaped groove near the terminal raphe endings. These morphological characteristics resemble those of the genus Labellicula, however, the presence of an internal marginal canal does not match Labellicula . The other Olifantiella species is identical to O. muscatinei, which possesses occluded fenestrulae on the valve face. The occurrences of these two Olifantiella species are the first records for the temperate Pacific region and their presence on a ship's hull indicates that Olifantiella spp. may be dispersed widely along shipping routes.